Design Of Geographic Information Systems Monitoring Waqf At The Cikupa Sub-District Religious Affairs Office - Harfizar, Harfizar; Mulyati, Mulyati; Fikri, Mohamad Ali (APTISI Transactions on Management (ATM), 2019)
Geographic Information System Technology (GIS) / Geographic Information System (GIS) is a technological information system regarding geography that is very developed up to the present. Geographic Information Systems have a very good ability in visualizing spatial data and its attributes, modifying shapes, colors, sizes, and symbols. GIS can be used by various fields of science, work, and events. Along with the advancement of information technology in the modern era, government services to the public must adapt to the demands of the times. Creativity and innovation as a form of service to the community are absolute and very necessary and one of them is by providing information technology-based services. The Office of Religious Affairs is an office that carries out part of the duties of the Indonesian Ministry of Religion office in the regencies and municipalities in the field of Islamic religious affairs within the sub-district. The purpose of this research is to improve the management of waqf assets by displaying the geographical locations of waqf land assets so that it is easier to monitor waqf assets so that their utilization can be maximized through the geographical information system at the Cikupa District Religious Affairs Office. Endowments are assets of the people who must be saved, managed well, and developed for useful purposes. The system analysis method used is PIECES which consists of Performance, Information, Economy, Control, Efficiency and Service. Unified modeling Language (UML) as a tool to analyze system rocedures that are running. With a geographic information system monitoring waqf land assets can display waqf assets contained in Cikupa District by displaying the location of waqf land through digital maps contained in geographic information systems.